Named Entity Recognition Based on Multi-Class Label Prompt Selection and Core Entity Replacement - Di Wu; Yao Chen; Mingyue Yan (Applied Sciences, 2025)
At present, researchers are showing a marked interest in the topic of few-shot named entity recognition (NER). Previous studies have demonstrated that prompt-based learning methods can effectively improve the performance of few-shot NER models and can reduce the need for annotated data. However, the contextual information of the relationship between core entities and a given prompt may not have been considered in these studies; moreover, research in this field continues to suffer from the negative impact of a limited amount of annotated data. A multi-class label prompt selection and core entity replacement-based named entity recognition (MPSCER-NER) model is proposed in this study. A multi-class label prompt selection strategy is presented, which can assist in the task of sentence–word representation. A long-distance dependency is formed between the sentence and the multi-class label prompt. A core entity replacement strategy is presented, which can enrich the word vectors of training data. In addition, a weighted random algorithm is used to retrieve the core entities that are to be replaced from the multi-class label prompt. The experimental results show that, when implemented on the CoNLL-2003, Ontonotes 5.0, Ontonotes 4.0, and BC5CDR datasets under 5-Way k-Shot (k = 5, 10), the MPSCER-NER model achieves minimum F1-score improvements of 1.32%, 2.14%, 1.05%, 1.32%, 0.84%, 1.46%, 1.43%, and 1.11% in comparison with NNshot, StructShot, MatchingCNN, ProtoBERT, DNER, and SRNER, respectively.